THE INFLUENCE OF LOCAL REVENUE, CAPITAL EXPENDITURE, AND BALANCE FUNDS ON REGIONAL FINANCIAL INDEPENDENCE IN ACEH PROVINCE - Alya Maulisa; Muttaqien; Ghazali Syamni; Wahyuddin (PT. Radja Intercontinental Publishing, 2025)
This study aims to analyze the effect of Regional Original Revenue (PAD), Capital Expenditure, and Balance Fund on Regional Financial Independence in Aceh Province for the period 2012-2023. This study uses secondary data from the Aceh Government Budget Realization Report which is analyzed by multiple linear regression methods. The results showed that PAD has a positive and significant effect on Regional Financial Independence, which indicates that an increase in local revenue is able to strengthen regional financial independence. In contrast, capital expenditure has a negative and significant effect, meaning that any increase in capital expenditure tends to reduce regional financial independence, especially if it is not supported by an increase in PAD. The Balance Fund also has a negative and significant effect, which means that the greater the funds received from the central government, the lower regional financial independence. Dependence on transfer funds reflects the weak ability of regions to finance government needs independently.